2017
DOI: 10.1002/ijgo.12403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on the incidence of perineal trauma

Abstract: Increased BMI at booking was associated with a reduced incidence of minor perineal trauma at delivery, but was not associated with OASIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
2
20
1
Order By: Relevance
“…Only a few studies are available that evaluated the impact of obesity on perineal trauma. However, in contrast to our findings, the studies reported obesity as a protective factor against both mild and severe forms of perineal injury [ 20 , 22 ]. The risk estimate of perineal tear in the study is consistent with the studies conducted in Slovenia and Saudi Arabia [ 21 , 41 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Only a few studies are available that evaluated the impact of obesity on perineal trauma. However, in contrast to our findings, the studies reported obesity as a protective factor against both mild and severe forms of perineal injury [ 20 , 22 ]. The risk estimate of perineal tear in the study is consistent with the studies conducted in Slovenia and Saudi Arabia [ 21 , 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, the reported associations are inconsistent. A few studies have reported that overweight is protective against perineal trauma [ 20 , 22 ], while others have suggested high risk for perineal injury [ 21 , 23 ]. Several studies, mainly from high-income countries, have investigated the impact of obesity on PPH and have reported a small [ 24 , 26 ] to a moderate increase of PPH odds [ 27 , 28 ] in obese women compared to the normal-weight women.…”
mentioning
confidence: 99%
“…The risk of episiotomy was lower in women who have had an increased BMI [ 48 ]. An increased BMI at enrolment was associated with a reduced incidence of minor perinatal trauma at delivery [ 49 ]. Obese women were less likely to use tobacco, were more likely to have their labor augmented or induced with oxytocin, and had shorter second stages than women who were not obese [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with recently published United Kingdom data, which report that higher BMI is protective for minor perineal trauma, but not for obstetric anal sphincter injuries. 39 Other studies, however, suggest that higher BMI is protective for obstetric anal sphincter injuries. 13,40 Birth position did not influence the rate of obstetric anal sphincter injuries in our study.…”
Section: Adjusted a Or (95% Ci)mentioning
confidence: 98%